Enhancing Efficiency in Inverted Quantum Dot Light-Emitting Diodes through Arginine-Modified ZnO Nanoparticle Electron Injection Layer - Young-Bin Chae; Su-Young Kim; Hyuk-Doo Choi; Dae-Gyu Moon; Kyoung-Ho Lee; Chang-Kyo Kim (Nanomaterials, 2024)
Many quantum dot light-emitting diodes (QLEDs) utilize ZnO nanoparticles (NPs) as an electron injection layer (EIL). However, the use of the ZnO NP EIL material often results in a charge imbalance within the quantum dot (QD) emitting layer (EML) and exciton quenching at the interface of the QD EML and ZnO NP EIL. To overcome these challenges, we introduced an arginine (Arg) interlayer (IL) onto the ZnO NP EIL. The Arg IL elevated the work function of ZnO NPs, thereby suppressing electron injection into the QD, leading to an improved charge balance within the QDs. Additionally, the inherent insulating nature of the Arg IL prevented direct contact between QDs and ZnO NPs, reducing exciton quenching and consequently improving device efficiency. An inverted QLED (IQLED) utilizing a 20 nm-thick Arg IL on the ZnO NP EIL exhibited a 2.22-fold increase in current efficiency and a 2.28-fold increase in external quantum efficiency (EQE) compared to an IQLED without an IL. Likewise, the IQLED with a 20 nm-thick Arg IL on the ZnO NP EIL demonstrated a 1.34-fold improvement in current efficiency and a 1.36-fold increase in EQE compared to the IQLED with a 5 nm-thick polyethylenimine IL on ZnO NPs.